2010
DOI: 10.1177/0897190010380745
|View full text |Cite
|
Sign up to set email alerts
|

Combating Counterfeit Medications

Abstract: The production and distribution of counterfeit medications has become a significant global public health issue and though not as rampant in the United States as in other parts of the world, the Food and Drug Administration (FDA) has seen a 10-fold increase in the number of cases investigated. The purpose of this study was to examine California pharmacist knowledge of counterfeit medications, impact of technology and barriers to pharmacist involvement, and potential roles pharmacists can undertake. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…As expected, pharmacists' ways to detect counterfeit medicines were limited to common packaging/labelling authentication features, which implies they lack sufficient skills and funds to improve their capability to detect counterfeit medicines in the pharmacy. Similar responses have been reported by pharmacists in both developing and developed countries (26,27). Furthermore, inadequate awareness of the pharmacists of current legislation in Egypt on anti-counterfeiting of medicines and medicine distribution is disturbing as this lack of knowledge may greatly affect their attitudes and practices.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As expected, pharmacists' ways to detect counterfeit medicines were limited to common packaging/labelling authentication features, which implies they lack sufficient skills and funds to improve their capability to detect counterfeit medicines in the pharmacy. Similar responses have been reported by pharmacists in both developing and developed countries (26,27). Furthermore, inadequate awareness of the pharmacists of current legislation in Egypt on anti-counterfeiting of medicines and medicine distribution is disturbing as this lack of knowledge may greatly affect their attitudes and practices.…”
Section: Discussionsupporting
confidence: 60%
“…A similar trend has been reported in other developing countries (26,28). In contrast, a survey of pharmacists in California, United States of America, indicated a much lower incidence stocking counterfeit medicines (27), which highlights the relationship between strong regulatory control and the extent of infiltration of counterfeit medicines into the legitimate supply system and good medicine purchasing practices.…”
Section: Discussionmentioning
confidence: 95%
“…SFM attitudes from this review were consistent with Law and Youmans, 38 noting 59.3% of pharmacists in California believed it is a serious issue; however, 60% had no SFM experience. Reporting in Sweden was lower than in California, as 52.4% of pharmacists would report the incident to the FDA, corporate headquarters or board of pharmacy.…”
Section: Discussionsupporting
confidence: 77%
“…Reporting in Sweden was lower than in California, as 52.4% of pharmacists would report the incident to the FDA, corporate headquarters or board of pharmacy. 38 This suggests SFM education is more available in the United States; however, both countries should encourage reporting to authorities and educating consumers.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus suggested that knowledge of regulatory references by Italian community pharmacists is at least limited. Studies addressing pharmacists’ awareness about falsified drugs have been performed so far in several countries, including California, Jordan, Iran, Yemen, Sudan, and Lebanon, however to our best knowledge this is the first investigation in Italy 27-32. Italian community pharmacists’ need for more information and educational programmes about falsified drugs is also suggested by about 33% of our respondents (mainly younger and females) being unable to estimate the circulation of these products in Italy.…”
Section: Discussionmentioning
confidence: 86%